Halymenia durvillei Extracts Exert Antiobesity Effects by Targeting hosl‐1‐Mediated Lipolysis in a Glucose‐Induced Caenorhabditis elegans Model - Kawita Chumphoochai; Sukrit Promtang; Pawanrat Chalorak; Preeyanuch Manohong; Nakorn Niamnont; Montakan Tamtin; Prasert Sobhon; Simon Tuck; Krai Meemon (eFood)
ABSTRACT The antiobesity effect of extracts from the marine algae, Halymenia durvillei (HD), was investigated in a glucose‐induced Caenorhabditis elegans model of obesity. Total fat accumulation, triglyceride levels, lifespan, intracellular ROS levels, and the potential mechanism of action of H. durvillei extracts were examined. The present study demonstrated that the ethanol fraction of H. durvillei (HDET) and ethyl acetate fraction of H. durvillei (HDEA) extracts led to a significant reduction in fat accumulation, triglyceride levels, the GFP‐labeled dhs‐3, a marker for lipid droplets, and the intracellular ROS levels. H. durvillei extracts significantly extended the lifespan of glucose‐induced worms. In addition, the mRNA expression of lipolysis‐related genes, atgl‐1 and hosl‐1, showed significant upregulation following treatment with H. durvillei extracts. This finding was supported by RNA interference (RNAi) of atgl‐1 and hosl‐1, which resulted in disrupting the effect of the H. durvillei extracts on lowering fat accumulation. Furthermore, transcriptomic analysis revealed diverse metabolic activities in glucose‐induced worms treated with HDEA, affecting fatty acid metabolism. The results suggested that these extracts provide an antiobesity effect mediated through the lipolysis genes, atgl‐1 and hosl‐1. H. durvillei‐derived extracts may offer valuable insights as functional food ingredients for use in the prevention of obesity.